Where parental perspective, practice, and reasoning meet : the relevance of home language development for parents with bilingual preschool-aged children in Iceland - Nichole Leigh Mosty 1972- (2013)
It is said that children who learn more than one language develop strong cognitive skills and diverse communication skills but often times take longer to learn those languages, and sometimes do not learn either language as well as monolingual language learners. Parents raising bilingual children don‘t necessarily calculate the advantages and disadvantages of their children learning more than one language. They are most often simply faced with making a decision based on the circumstances of their lives. The perspectives that parents hold regarding home language development most often affect how they behave in relation to home language development. If parents have a positive perspective about home language they will most likely be motivated to teach their children their home language. Preschool-aged children are in the throngs of language acquisition, making it all the more important for parents who speak a minority home language to make informed and conscious decisions about home language development. This is a mixed method study where 43 participants took a quantitative survey with questions pertaining to perspective, language use, home language environment, and reasoning for home language development. Six participants also sat for qualitative interviews. In this study the researcher set out to learn what perspectives parents held about home and bilingual language development, how they practiced language development in the home environment, and what reasons parents had for home and bilingual language development. Results indicated that parents had overwhelmingly positive perspectives about both home language and Icelandic development, that parents used socializing and communication both as method and motivator for language development, parents made conscious decisions as to why and how the home language was used, and travel to the home country was important to parents as it linked home language development with cultural and personal identity. Því hefur verið haldið fram að börn sem læra fleiri en eitt tungumál ...